Research methods in theatre and performance - Kershaw, Baz; Nicholson, Helen, 1958- (Research methods for the arts and humanities., 2011)
How have theatre and performance research methods and methodologies engaged the expanding diversity of performing arts practices? How can students best combine performance/theatre research approaches in their projects? This book's 29 contributors provide hands-on answers to such questions. Challenging and debating received research wisdom and exploring innovative procedures for rigorous enquiry via archives, technology, practice-as-research, scenography, performer training, applied theatre/performance, body in performance and more, they create a focussed compendium of future research options. Key Features Created in association with TaPRA, the leading UK Theatre and Performance Research organisation, with chapters produced by specialist groupings. Provides many detailed project case studies and examples -- including successful practice-based PhDs -- plus analysis of dynamic couplings between methods, methodologies and skill-sets. Introduction interrogates crucial qualities of performing arts research that constitute theatre and performance as, variously, single-, multi-, inter-, and trans-disciplinary. Contributors include: Maggie B. Gale (Chair of Drama, University of Manchester); Steve Dixon (Professor of Digital Performance, Brunel University); Joanne 'Bob' Whalley and Lee Miller (University Lecturers and founders Fictional Dogshelf Theatre Company); Simon Ellis and Rosemary Lee (independent performance/dance makers); Roberta Mock (Professor of Performance, University of Plymouth).